Lanthanide luminescent gold nanoparticles: pH-driven self-assembly formation between Eu(III)-cyclen conjugated AuNPs and sensitising β-diketonate antenna in water - GUNNLAUGSSON, THORFINNUR (My University, 2009)
The formation of a self-assembly between water soluble gold nanoparticles AuNP-1.Eu, functionalised with a heptadentate macrocyclic Eu(III) cyclen conjugate via an alkyl thiol spacer, and a naphthalene -diketone antenna was investigated as a function of pH in water. In the study, the changes in the absorption spectra of the antenna and the gold surface plasmon resonance band, the fluorescence and the delayed Eu(III) emission of the self-assembly were all monitored. We demonstrate that the Eu(III) emission arising from the self-assembly formation on AuNP is significantly modulated as a function of pH, where within the physiological pH range, the emission is switched on and that a direct connection can be made between theses changes and the quenching in the antenna as a function of pH.
PUBLISHED
Keywords: Chemistry